Effect of Steam Blanching, Dehydration Temperature & Time, on the Sensory and Nutritional Properties of a Herbal Tea Developed from Moringa oleifera Leaves - Wickramasinghe, Yasara W. H. (Int J Food Sci, 2020)
The core purpose of the current study is to explore the use of Moringa oleifera leaves, to produce a herbal tea with acceptable sensory properties and nutritional properties by utilizing the steam blanching technique, different dehydration temperatures and time, which can be accepted in the Sri Lankan market. Six sets of samples were prepared where temperature and time combinations were 55°C—6 h, 60°C—4.30 h, 65°C—3 h for the unblanched samples & 55°C—6 h, 60°C—5.30 h & 65°C—4 h for the steam blanched samples. These samples were evaluated, employing a trained panel of 5 tea tasters and a semi trained panel of 35 members. The sample code 706 (steam blanched, 65°C—4 h) was selected as the sample with best sensory attributes. The blanched and unblanched samples dried at 65°C were tested for their proximate, mineral, vitamin, antioxidant and phytochemical contents. The effects of steam blanching on these two samples were evaluated & compared. This study highlights that steam blanching significantly increased the carbohydrates, fat, Mn, Fe, vitamin A, vitamin E and the DPPH scavenging activity whereas steam blanching significantly reduced the protein, fiber, Na, K, Ca, Total phenolic contents and flavonoids content but vitamin C, Zn, Cu and Mg contents were unaffected by steam blanching.